Satisfaction as Mediator Variable Linking Service Quality to Customer Loyalty in Animal Hospital in Rangsit Municipality, Pathum Thani Province - Phengthi, Siriphon; Ramanust, Sumalee (Journal of Industrial Business Administration, 2024)
The objectives of this article are 1) to study the level of service quality, satisfaction and loyalty of users to the animal hospital in Rangsit Municipality, Pathum Thani province and 2) to study the satisfaction as the mediator factor linking the service quality to the loyalty of users of the animal hospital in Rangsit Municipality, Pathum Thani province.3) to study service quality and satisfaction that have a direct influence on the loyalty of users of an animal hospital in Rangsit Municipality. Pathum Thani Province As the quantitative research, the research tool used is a questionnaire. The researcher collected data from 200 customers receiving services at an animal hospital in Rangsit Municipality, Pathum Thani province, according to the concept of Hair et al. (2006). Statistics used in research for data analysis include frequency, percentage, mean and standard deviation. In addition, the structural equation analysis (SEM) is conducted by using the Smart PLS program. As research results, it was found that 1) the levels of the service quality, satisfaction, and loyalty of service users are overall at a high level with the means respectively, and the standard deviations of 0.620, 0.710, and 0.645, respectively, and 2) the satisfaction is the mediator factor linking the service quality to the customer loyalty. The service quality (SQ) and the satisfaction (ST) of the animal hospital in Rangsit Municipality, Pathum Thani province, have a direct influence on the loyalty (LO) with the values of 0.817 and 0.316, respectively, and the service quality (SQ) has an indirect influence on the loyalty (LO) with the value of 0.258.